Fatigue Life Prediction Of Minibus Lower Suspension Arm Using Strain-Life Approach - Anh, Nguyen Thi Mai; Đức, Phạm Văn (Yayasan Kawanad, 2025)
The lower suspension arm is a critical component in vehicle suspension systems that experiences complex dynamic loads during operation. This study aims to predict the fatigue life of minibus lower suspension arms using a strain-life approach considering road conditions in Southeast Asia. The finite element method was employed to analyze stress and strain distributions on the component, while fatigue failure criteria were applied to predict component life. Simulations were conducted using ANSYS software with Al-Si aluminum alloy material commonly used in suspension components. Analysis results showed that maximum stress occurred at the bushing joint area with a value of 245 MPa, and fatigue life was predicted to reach 1.2 × 10⁶ cycles for rough road conditions. Sensitivity analysis indicated that road roughness and joint geometry have significant influences on component fatigue life. This research contributes to design optimization and material selection to enhance lower suspension arm durability under tropical operating conditions.